2021
DOI: 10.1001/jama.2021.2536
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Low-Intensity vs High-Intensity Home-Based Walking Exercise on Walk Distance in Patients With Peripheral Artery Disease

Abstract: IMPORTANCE Supervised high-intensity walking exercise that induces ischemic leg symptoms is the first-line therapy for people with lower-extremity peripheral artery disease (PAD), but adherence is poor.OBJECTIVE To determine whether low-intensity home-based walking exercise at a comfortable pace significantly improves walking ability in people with PAD vs high-intensity home-based walking exercise that induces ischemic leg symptoms and vs a nonexercise control.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
198
0
3

Year Published

2021
2021
2021
2021

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 133 publications
(201 citation statements)
references
References 39 publications
0
198
0
3
Order By: Relevance
“…A search of the literature identified a total of 8693 studies, of which 27 were included in the full review following screening (online supplementary material). Twelve of the included studies were randomised controlled trials, [22][23][24][25][26][27][28][29][30][31][32][33] and the remaining 15 were nonrandomised. [34][35][36][37][38][39][40][41][42][43][44][45][46][47][48] The included studies comprised a total of 2351 participants, 1642 of whom received a home-based intervention, representing a total of 147,810 patient-hours.…”
Section: Study Selectionmentioning
confidence: 99%
“…A search of the literature identified a total of 8693 studies, of which 27 were included in the full review following screening (online supplementary material). Twelve of the included studies were randomised controlled trials, [22][23][24][25][26][27][28][29][30][31][32][33] and the remaining 15 were nonrandomised. [34][35][36][37][38][39][40][41][42][43][44][45][46][47][48] The included studies comprised a total of 2351 participants, 1642 of whom received a home-based intervention, representing a total of 147,810 patient-hours.…”
Section: Study Selectionmentioning
confidence: 99%
“…Many authors suggest that effective home-based exercise programs for individuals suffering from diabetes complicated with PAD may require ongoing contact with a physiotherapist, at least during the first six months [ 24 , 47 , 56 , 64 ], to consolidate good habits in patients and to confirm how to perform marching exercises well. A study published in April 2021 by McDermott et al identified the need for home-based exercise in patients with PAD and demonstrated the higher effectiveness of high intensity of these exercises [ 65 ]. The effectiveness of home exercise therapy was also confirmed in a study by Fukaya et al [ 66 ].…”
Section: Kinesitherapymentioning
confidence: 99%
“…Ninety patients confirmed diagnoses with COVID-19 were consulted at Al-Kindy Teaching Hospital (Al-Shifa center) from October 2020 till April 2021. All patients in this study were from Baghdad, diagnosed according to the WHO procedure [10].…”
Section: Study Design and Participantsmentioning
confidence: 99%